Debate about asessment practices in artistic disciplines - Lucia Ginochio Castro (Pontificia Universidad Católica del Perú, 2017)
This essay presents the debate about assessment practices in artistic disciplines in the context of higher education. It exposes the challenges of assessment in the arts and discusses the necessity to clarify its objectives. It also presents some assessment proposals that try to reconcile the debate. These proposals are analysed in relation to their applicability to improve the assessment processes in higher education. Finally, departing form this analysis, it offers recommendations to enhance evaluation processes in higher education. Given the recent foundation of the Performing Arts Faculty of PUCP, and considering PUCP's long tradition in fine arts disciplines, this topic is considered of great interest for the pedagogy of the arts and assessment in general.